The Role of Opioid Prescription in Incident Opioid Abuse and Dependence Among Individuals with Chronic Non-Cancer Pain: The Role of Opioid Prescription - Edlund, Mark J. (2014)
OBJECTIVE: Increasing rates of opioid use disorders (abuse and dependence) among patients prescribed opioids are a significant public health concern. We investigated the association between exposure to prescription opioids and incident opioid use disorders (OUDs) among individuals with a new episode of a chronic non-cancer pain (CNCP) condition. METHODS: We utilized claims data from the HealthCore Database for 2000–2005. The dataset included all individuals aged 18 and over with a new CNCP episode (no diagnosis in the prior 6 months), and no opioid use or OUD in the prior 6 months (n=568,640). We constructed a single multinomial variable describing prescription opioid days supply (none, acute, and chronic) and average daily dose (none, low dose, medium dose, and high dose), and examined the association between this variable and an incident OUD diagnosis. RESULTS: Patients with CNCP prescribed opioids had significantly higher rates of OUDs compared to those not prescribed opioids. Effects varied by average daily dose and days supply: low dose, acute (odds ratio (OR)=3.03, 95% confidence interval (CI)= 2.32, 3.95); low dose, chronic (OR=14.92, 95% CI=10.38, 21.46); medium dose, acute (OR=2.80, 95% CI=2.12, 3.71); medium dose, chronic (OR=28.69, 95% CI=20.02, 41.13); high dose, acute (OR=3.10 95% CI=1.67, 5.77); and high dose, chronic (OR=122.45, 95% CI=72.79, 205.99). CONCLUSION: Among individuals with a new CNCP episode, prescription opioid exposure was a strong risk factor for incident OUDs; magnitudes of effects were large. Duration of opioid therapy was more important than daily dose in determining OUD risk.